Land Management Change as Adaptation to Climate and Other Stressors: A Systematic Review of Decision Contexts Using Values-Rules-Knowledge - Nicholas A. Kirk; Nicholas A. Cradock-Henry (Land, 2022)
Agricultural producers are already experiencing the adverse effects of climate change, highlighting the urgent need for adaptation. While incremental changes to cope with interannual variability are widely applied, there is limited understanding of the social contexts that inform, enable, or constrain more transformational adaptations in response to anticipated or actual climate change and other stressors. Systematic review methods are used to identify 31 empirical examples of land management change as an adaptation response by agricultural producers in developed countries. We then applied the values-rules-knowledge (vrk) framework to analyse interactions between societal values, institutional rules, and scientific and experiential knowledge. The vrk is a heuristic to help decision makers analyze how the social system shapes their decision context. Three propositions highlighting the relative influence of different values–rules, values–knowledge, and rules–knowledge relationships on agri-food and forestry land-management decisions are presented and discussed. We suggest that further testing of these propositions will provide evidence for decision makers about how decision contexts can be shifted to enable anticipatory transformative adaptation in the primary industries and support sustainable transitions towards more resilient futures.